The Influence Volatility, Profitability, Carbon Intensity on Stock Returns in Mining Companies 2021-2023 - Prakoso, Satrio Budi; Suherman, Ujang; Pranata, Rengga Madya (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
Study This analyze influence volatility price share, profitability, and intensity carbon on the stock returns of Indonesian mining companies 2021–2023 using quantitative methods. Secondary data from report finance and trading share IDX, study This take sample 15 company with purposive sampling. The regression results show that while stock volatility has no effect and is not significant (coefficient 0.002 with significance 0.845>0.05), profitability has a positive and significant effect. to return share (coefficient 1,712 with significance 0.009 (<0.05), While That, carbon intensity Which measured through disclosure emission carbon Also No influential (coefficient -1,290 with a significance of 0.499 (>0.05),). In conclusion, profitability is a factor the main thing that improves attractiveness share, whereas volatility and emission carbon No influential. Implications study This emphasizes the importance of financial performance the good one and increasing environmental awareness for sustainability mining sector.